2009
DOI: 10.1177/1062860609332369
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Compliance Rates in the United States—A One-Year Multicenter Collaboration Using Product/Volume Usage Measurement and Feedback

Abstract: Hand hygiene (HH) is the single most important factor in the prevention of health care-acquired infections. The 3 most frequently reported methods of measuring HH compliance are: (1) direct observation, (2) self-reporting by health care workers (HCWs), and (3) indirect calculation based on HH product usage. This article presents the results of a 12-month multicenter collaboration assessing HH compliance rates at US health care facilities by measuring product usage and providing feedback about HH compliance. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 21 publications
2
59
1
2
Order By: Relevance
“…Product usage can also be compared with the industry-average volume of a single dose of product in estimating adherence rates. 36,55,56 Product measurement can be hampered by unreliable usage data from distribution or materials management or intentional tampering with dispensers or deliberate waste of product. B.…”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…Product usage can also be compared with the industry-average volume of a single dose of product in estimating adherence rates. 36,55,56 Product measurement can be hampered by unreliable usage data from distribution or materials management or intentional tampering with dispensers or deliberate waste of product. B.…”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…Good hand hygiene plays a major role in reducing and eliminating the spread of germs and infections from patient-topatient. Research has shown that while healthcare workers state largely favorable attitudes towards hand-cleaning practices, observed compliance rates are below 30% [1]. Reasons given by professionals for the lack of compliance to hand-cleaning practices highlights several explanatory factors, including: work conditions (lack oftime), infrastructures (lack of equipment), training (inadequate), human environment (superiors, colleagues, unscrupulouspatients) and the health of medical and nursing staff (skin irritations caused by frequent hand-cleaning).…”
mentioning
confidence: 99%
“…A multicentre, one-year evaluation of a model using education and reminders as a route to empowerment, found a statistically significant increase in hand hygiene compliance with the model working equally well for all sizes of hospitals and unit types. 1140 Posters, another form of reminder, are used in hand hygiene programmes and campaigns to educate and empower HCWs as well as patients. An evaluation of 69 hand hygiene posters representing 75 messages found that only 41% framed the message for motivation, empowerment, and health promotion.…”
Section: Reminders and Motivational Messagesmentioning
confidence: 99%